Impairment of EQ-5D-5L Domains According to Allergic Rhinitis and Asthma Control: A MASK-air Real-World Study - Sousa-Pinto, Bernardo (2023)
EQ-5D-5L (EuroQOL, 5 Domains, 5 Levels) is a widely used health-related quality-of-life instrument, comprising 5 domains. However, it is not known how each domain is impacted by rhinitis or asthma control.